Experimental Research on Mechanical Property and Environmental Safety of an Industrial Residue Waste Subgrade Material - Yangpeng Zhang; Jianping Xiong; Qinglin Li; Jiuhui Cui (Advances in Materials Science and Engineering)
In order to promote the sustainable use of oil shale residues, a novel subgrade material (SOF) composed of silty clay, oil shale ash residue, and fly ash was developed. The aim of this paper is to study the mechanical behavior and environmental impact of SOF, which is regarded as the safety assessment and prediction for the application of this novel material. To this purpose, the road performance, dynamic properties, and environment impact tests are conducted. In terms of the road performance, the test results of SOF exceed the standard requirement, especially for CBR (California bearing ratio), which can maintain good performance at bad conditions of low compaction degree and being soaked for a long time. The dynamic properties under cyclic loadings are better than most of original and stabilized soils. The shear strength parameters and the anti-damage mechanism are also discussed; research results show that the friction of SOF mostly contributes to shear strength under high stress conditions, while its cohesion tends to play a more important role under low stress conditions. According to the deformation variation, the accumulation settlement of SOF under vehicle loadings after several years is predicted, which is far lower than the limit of expressway and Grade I highway. Furthermore, the chemical stability and toxicity of SOF leachates are environmentally friendly, which are in line with the benchmarks of Class II surface water and Class III ground water. All the experimental results manifest that SOF used as subgrade filling has good application potential and safety.